Koizumi and Japanese Politics : Reform Strategies and Leadership Style. - Uchiyama, Yu (Routledge/University of Tokyo series., 2010)
An empirical and theoretical study of the Koizumi administration, covering such issues as the characteristics of its political style, its domestic and foreign policies, and its larger historical significance. It is suitable for scholars and students with an interest in comparative politics, administrative reform, and contemporary Japan.